Enhancing prognostic prediction in hepatocellular carcinoma post-TACE: a machine learning approach integrating radiomics and clinical features - Zhang, Mingqi; Kuang, Bingling; Zhang, Jingxuan; Peng, Jingyi; Xia, Haoming; Feng, Xiaobin; Peng, Liang (Frontiers in Medicine, 2024)
Objective: To investigate the use of radiomics features and clinical information by four machine learning algorithms for predicting the prognosis of patients with hepatocellular carcinoma (HCC) who have been treated with transarterial chemoembolization (TACE).Methods: A total of 105 patients with HCC treated with TACE from 2002 to 2012 were enrolled retrospectively and randomly divided into two cohorts for training (n = 71) and validation (n = 34) according to a ratio of 7:3. The Spearman rank, random forest, and univariate Cox regression were used to select the optimal radiomics features. Univariate Cox regression was used to select clinical features. Four machine learning algorithms were used to develop the models: Random Survival Forest, eXtreme Gradient Boosting (XGBoost), Gradient Boosting, and the Cox Proportional Hazard Regression model. The area under the curve (AUC) and C-index were devoted to assessing the performance of the models in predicting HCC prognosis.Results: A total of 1,834 radiomics features were extracted from the computed tomography images of each patient. Age at diagnosis, TNM stage, and metastasis were clinical risk factors for HCC prognosis that were analyzed using univariate Cox regression. In various models, the efficacy of the combined models generally surpassed those of the radiomics and clinical models. Among four machine learning algorithms, XGBoost exhibited the best performance in combined models, achieving an AUC of 0.979 in the training set and 0.750 in the testing set, demonstrating its strong prognostic prediction capability.